Pheophorbide b ethyl ester from a chlorella vulgaris dietary supplement. - Chee, Chin Fei; Abd Rahman, Noorsaadah; Zain, Sharifuddin Md; Ng, Seik Weng (International Union of Crystallography, 2008)
In the title compound, C(37)H(38)N(4)O(6), four five-membered nitro-gen-bearing rings are nearly coplanar. Two N atoms in two these five-membered rings have attached H atoms, which contribute to the formation of intra-molecular N-H⋯N hydrogen bonds [N⋯N = 2.713 (5)-3.033 (6) Å].